The controversial dynamics of Colombian scientific policy 1990-2017: a sociological approach - Chávarro, Luis Alfonso (2020)
This article synthesizes an investigation on the appropriation of the international model of innovation in Colombian Scientific Policy and the controversial dynamics generated after its implementation. The mode of analysis adopted lies in an integration by a combination of micro approaches (representations and controversies), with macro approaches (world culture and field theory), articulated to a methodological procedure in which an index of controversiality is proposed as a novelty, And after that, results emerge that show how the dissemination of the international model focused on innovation has been effective, but that given its emphasis on the economic utility of science, it has ended up generating controversies among scientific agents, linked to the incipient social world of science in Colombia, showing a perception of discomfort. Given this discovery, the discussion suggests how an alternative citizen model of scientific policy could be, where the economic representation of innovation is balanced with social and environmental innovation.